Spring coccolithophore production and dispersion in the temperate eastern North Atlantic Ocean - Schiebel, Ralf; Brupbacher, Ursula; Schmidtko, Sunke; Nausch, Günther; Waniek, Joanna; Thierstein, Hans-R. (Journal of Geophysical Research, 2011)
International audience Production and dispersion of coccolithophores are assessed within their ecologic and hydrographic context across enhanced spring chlorophyll production in the surface eastern North Atlantic. Within a 4 day period from 12 to 16 March 2004, a N-S transect from 47N to 33N was sampled along 20W. Water samples from defined depths down to 200 m were analyzed for coccolithophores from 0.45 m polycarbonate filters by scanning electron microscopy. At 47N coccolithophores flourished when euphotic conditions allowed new production at deep mixing, low temperatures, and high nutrient concentrations. Emiliania huxleyi flourished at high turbulence during an early stage of the phytoplankton succession and contributed half of the total coccolithophore assemblage, with up to 150 × 103 cells L-1 and up to 12 × 109 cells m-2 when integrated over the upper 200 m of the water column. Maximum chlorophyll concentrations occurred just north of the Azores Front, at 37N-39N, at comparatively low numbers of coccolithophores. To the south, at 35N-33N, coccolithophores were abundant within calm and stratified Subtropical Mode Waters, and E. huxleyi was the dominant species again. Although the cell densities of coccolithophores observed here remained below those typical of plankton blooms visible from satellite images, the depth-integrated total mass makes them significant producers of calcite and contributors to the total carbon sedimentation at a much wider range of ecological conditions during late winter and early spring than hitherto assumed